ALIXON TORA SOGUNIY - Samadova Nargiza Mukhiddinovna (Galaxy International Interdisciplinary Research Journal, 2021)
In this article you will learn about the life of Alikhan Tora and about escape from prison, and its role in the formation of ETR (East Turkestan Revolution). creations and books.